Gender Relations in Korea Today in the Light of Schleiermacher’s Ethics of Solidarity and the Unfolding of the Holy Spirit - Park, Kwangwoo (International journal of public theology, 2025)
This study examines Schleiermacher’s perspective on Christian gender relations in relation to the context of Korean society, where conflicts between men and women are increasingly prevalent. It seeks to reconcile such conflicts. Schleiermacher considers gender relations in terms of the unfolding of humanity, which involves recognizing the individuality of both men and women and their collaboration. Christians bear the Holy Spirit in accordance with their individuality and express its unity through mutual communication. Christian gender relations are to be understood in terms of the unfolding of the Holy Spirit, whereby Christians sanctify each other through their communication, forming His unity and advancing through their union. With its critical reinterpretation, Schleiermacher’s model of Christian gender relations, understood in solidarity for the unfolding of the Holy Spirit as the meta-perspective, highlights the necessity of collaboration and solidarity between men and women for the common good in Korea.